1996
DOI: 10.1021/ef9501408
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pressure on the Thermal Cracking of Oil

Abstract: The influence of pressure on gas, liquid, and solid products of thermal cracking of a C9+ fraction of a saturate-rich Devonian oil from the Western Canada Basin has been investigated. Confined pyrolysis was performed in sealed gold tubes at 350, 380, and 400 °C and pressures ranging from 90 to 2000 bar for 72 h. At the temperatures investigated, the effect of pressure on oil cracking and product generation is small. Rates of early hydrocarbon gas generation (350 and 380 °C, 72 h) decrease with increasing press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 35 publications
0
46
1
Order By: Relevance
“…The magnitude of the retardation effects of pressure on the initial stages of oil cracking is much greater than found in previous studies using confined gold bags pyrolysis method (Hill et al, 1996;Al Darouich et al, 2006) that generally show less retardation effect compared to the unconfined water pyrolysis method used here. The decomposition of oil to gas occurs via beta scission of hydrocarbons to generate free radicals.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…The magnitude of the retardation effects of pressure on the initial stages of oil cracking is much greater than found in previous studies using confined gold bags pyrolysis method (Hill et al, 1996;Al Darouich et al, 2006) that generally show less retardation effect compared to the unconfined water pyrolysis method used here. The decomposition of oil to gas occurs via beta scission of hydrocarbons to generate free radicals.…”
Section: Discussioncontrasting
confidence: 70%
“…At lower pressures, Fabuss et al (1964) concluded that pressure accelerates cracking between 1 and 400 bar while a decrease was observed at higher pressure (800 bar). This trend of an initial increase followed by a decrease at higher pressure has been confirmed for oil cracking (Behar and Vandenbroucke, 1996;Hill et al, 1996). On the contrary, Jackson et al (1995) observed a continuous retarding effect for n-hexadecane pyrolysis between 120 and 600 bar.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…41 The model of activation volume is included to account for such effects, which has been elaborated in the previous works. 31,42 Thus, the gas yields at 470-900 bars are lower than at 200…”
Section: Pressure Effects On Gas Yieldsmentioning
confidence: 96%
“…On the other hand, concentrations and collision rates of reactants would be enhanced with increasing pressure, resulting in increased overall reaction rates. 31 Although cage/diffusional effects generally retard reaction rates with increasing pressure, collision rates among reactants will increase with pressure and reach a maximum at a given pressure threshold, resulting in increased reaction rates and gas yields. 31 This could be the case in this study, which shows higher yields at 750 bar than at 470 bar when oil cracks at the elevated stage in the wet gas window.…”
Section: Pressure Effects On Gas Yieldsmentioning
confidence: 99%